Pengaruh Media Sosial dan Self Confidence terhadap Kesehatan Mental Siswi SMA 1 Kecamatan Seluma - Elma Nengsi, Rice; Febrian Nasution, Alif; Fajar Saputra, Rian (DAWUH : Islamic Communication Journal, 2023)
This study aims to test whether there is an influence of social media and self-confidence on mental health among teenagers in Seluma sub-district. This research uses a quantitative method, the data collection technique is by distributing a questionnaire with 30 items distributed. Data collection amounted to 130 respondents. This research was analyzed using quantitative analysis using SPSS 22 by testing regression, correlation, normality test, reliability test, and R square. Based on the results of this study, it shows that the influence of social media and self-confidence on mental health is in the weak category, namely 14.3%.